2015
DOI: 10.1088/0067-0049/217/2/26
|View full text |Cite
|
Sign up to set email alerts
|

The Lick Agn Monitoring Project 2011: Spectroscopic Campaign and Emission-Line Light Curves

Abstract: In the Spring of 2011 we carried out a 2.5 month reverberation mapping campaign using the 3 m Shane telescope at Lick Observatory, monitoring 15 low-redshift Seyfert 1 galaxies. This paper describes the observations, reductions and measurements, and data products from the spectroscopic campaign. The reduced spectra were fitted with a multicomponent model in order to isolate the contributions of various continuum and emission-line components. We present light curves of broad emission lines and the AGN continuum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
266
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(280 citation statements)
references
References 121 publications
13
266
1
Order By: Relevance
“…We constructed a separate reference spectrum for each telescope by averaging the highest-S/N spectra in each data set and then broadened the reference spectrum so that the Barth et al (2015) found F var values ranging from 0.5% to 3.3% for individual AGNs in the 2011 Lick AGN Monitoring Project. Figure 2 shows (in black) the mean and rms residual spectra for the MDM data set.…”
Section: Spectral Flux Calibrationsmentioning
confidence: 99%
See 3 more Smart Citations
“…We constructed a separate reference spectrum for each telescope by averaging the highest-S/N spectra in each data set and then broadened the reference spectrum so that the Barth et al (2015) found F var values ranging from 0.5% to 3.3% for individual AGNs in the 2011 Lick AGN Monitoring Project. Figure 2 shows (in black) the mean and rms residual spectra for the MDM data set.…”
Section: Spectral Flux Calibrationsmentioning
confidence: 99%
“…Both the broad Hβ and He II λ4686 emission lines exhibit strong variations, and the Hβ rms profile appears to have multiple peaks. Traditionally, the rms spectrum is constructed such that the value at each wavelength is taken to be the standard deviation of fluxes from all epochs, but this does not take into account Poisson or detector noise, which may bias the rms profile by a small amount (Barth et al 2015). Park et al (2012b) suggest using the S/N for each spectrum as the weight for that spectrum in calculating the rms, or using a maximum-likelihood method to obtain the rms.…”
Section: Spectral Flux Calibrationsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the absorbers were large enoughthey could temporarily convert a pure Type 1 AGN into a Type 1.8 or 1.9 by eclipsing the broad components of b H (Osterbrock 1981), making a socalled "changing-look" AGN. To date,only a small number of changing-look Seyfert 1 s have been found, and they all show the nonstellar continuum emission weakening dramatically when the broad line components fade or even disappear (Collin-Souffrin et al 1973; Tohline & Osterbrock 1976;Lyutyj et al 1984;Cohen et al 1986;Storchi-Bergmann et al 1993;Aretxaga et al 1999;Eracleous & Halpern 2001;Denney et al 2014;Sanmartim et al 2014;Barth et al 2015). Even factor of twochanges in broad b H are rare in Seyfert 1ʼs, having been seen in only about 4% of the pairs of repeated observations in a sixyears longmonitoring campaign of 13 AGN (Rosenblatt et al 1992).…”
Section: Introductionmentioning
confidence: 99%